2016
DOI: 10.18632/oncotarget.9579
|View full text |Cite
|
Sign up to set email alerts
|

Indolin-2-one compounds targeting thioredoxin reductase as potential anticancer drug leads

Abstract: Several compounds bearing the indolinone chemical scaffold are known to possess anticancer properties. For example, the tyrosine kinase inhibitor sunitinib is an arylideneindolin-2-one compound. The chemical versatility associated with structural modifications of indolinone compounds underlies the potential to discover additional derivatives possessing anticancer properties. Previously synthesized 3-(2-oxoethylidene)indolin-2-one compounds, also known as supercinnamaldehyde (SCA) compounds in reference to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…We also identified that several of the compounds stabilized reduced TrxR1 in vitro , at least for Stattic, LLL12 and Cryptotanshinone, because they acted as redox cycling substrates with the otherwise covalently inhibited TrxR1. This type of effect with redox cycling of inhibited forms of TrxR1 was previously reported for several other compounds including juglone, dinitrohalobenzenes, curcumin, TRi-1, and indolin-2-one compounds [ 34 , [49] , [50] , [51] , [52] ]. Forms of TrxR1 with a covalently targeted Sec-residue and inhibited normal TrxR1 activity, but with maintained capacity for redox cycling through an NADPH oxidase activity, were collectively coined SecTRAPs (Selenium compromised thioredoxin reductase-derived apoptotic proteins) and formation of SecTRAPs may yield therapeutic effects either through cytotoxicity against cancer cells or by Nrf2 activation in normal cells [ 17 , 26 , 34 ].…”
Section: Discussionsupporting
confidence: 75%
“…We also identified that several of the compounds stabilized reduced TrxR1 in vitro , at least for Stattic, LLL12 and Cryptotanshinone, because they acted as redox cycling substrates with the otherwise covalently inhibited TrxR1. This type of effect with redox cycling of inhibited forms of TrxR1 was previously reported for several other compounds including juglone, dinitrohalobenzenes, curcumin, TRi-1, and indolin-2-one compounds [ 34 , [49] , [50] , [51] , [52] ]. Forms of TrxR1 with a covalently targeted Sec-residue and inhibited normal TrxR1 activity, but with maintained capacity for redox cycling through an NADPH oxidase activity, were collectively coined SecTRAPs (Selenium compromised thioredoxin reductase-derived apoptotic proteins) and formation of SecTRAPs may yield therapeutic effects either through cytotoxicity against cancer cells or by Nrf2 activation in normal cells [ 17 , 26 , 34 ].…”
Section: Discussionsupporting
confidence: 75%
“… • Sleep-wake cycle modulator (Olthof et al 2001 ) (Upadhyay and Mohan Rao, 2013 ) Chrysoeriol 30667 0.49 0.16 0.92 • Antioxidant • Anti-inflammatory(Inhibits lipid peroxidation, inhibits production of superoxide anion by xanthine/xanthine oxidase system, inhibits the lipopolysaccharideinduction of the nitric oxide synthase (iNOS) gene.) (Mishra et al 2003 ) (Choi et al 2005 ) Cinnamate 00930 0.31 0.12 0.18 • Antimicrobial (anti-mycobacterial agent that can be developed against tuberculosis) • Cancer chemopreventive (anti-proliferative activity against melanoma cells and lung carcinoma cells, inhibition of histone deacetylases in colon cancer cells) • Anti-obesogenic • Anti-hypertensive (inhibits serum lipase and angiotensin-converting enzyme) • Cardio-protective (In electrocardiography, it decreases the ST segment elevation induced by acute myocardial ischemia) • Antioxidant • Anti-inflammatory (Y. L. Chen et al 2011 ) (Zhu et al 2016 ) (Mnafgui et al 2015 ) (Song et al 2013 ) Ergothioneine a 03045 ND 0.79 0.99 • Antioxidant (Aruoma et al 2012 ) Ferulate 00954 6.22 10.28 19.69 • Antioxidant (Kanski et al 2002 2002) Indolin-2-one - 1.19 0.30 3.80 • Cancer chemopreventive (anti-proliferative and inhibits thioredoxin reductase (TrxR)) (Kaminska et al 2016 ) Luteolin 05800 ND 0.04 1.67 • Antioxidant (scavenges ROS) • Antimicrobial (broad spectrum gram positive bacteriostatic properties and yeast) (Lin et al 2008 ...…”
Section: Resultsmentioning
confidence: 99%
“…Chew and co‐workers developed two lead compounds ( 271–272 , Figure ) with N ‐butyl and N ‐benzyl substituent by screening a small library of indolin‐2‐one compounds. Both compounds showed potent inhibition of TrxR (Table ) and antiproliferative activities (Table ) . Yuan and co‐workers developed a series of (2E)‐(2‐oxo‐1, 2‐dihydro‐3H‐indol‐3‐ylidene) acetate derivatives and explored their inhibitory activity against several cancer cell lines.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%